2011
DOI: 10.1209/0295-5075/95/50004
|View full text |Cite
|
Sign up to set email alerts
|

The 1/N expansion of colored tensor models in arbitrary dimension

Abstract: In this paper we extend the 1/N expansion introduced in [1] to group field theories in arbitrary dimension and prove that only graphs corresponding to spheres S D contribute to the leading order in the large N limit.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
266
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(270 citation statements)
references
References 37 publications
4
266
0
Order By: Relevance
“…This dominance was already observed in so-called "tensor models", and have been studied extensively in the literature [31][32][33][34][35][36][37][38][39][40][41]. Previously, except for [31], only bosonic tensor models had been considered with various form of interactions.…”
Section: Jhep08(2017)083mentioning
confidence: 87%
“…This dominance was already observed in so-called "tensor models", and have been studied extensively in the literature [31][32][33][34][35][36][37][38][39][40][41]. Previously, except for [31], only bosonic tensor models had been considered with various form of interactions.…”
Section: Jhep08(2017)083mentioning
confidence: 87%
“…Despite some initial pessimism [177], a recent spike of optimism occurred within the growing tensor model community, when it was discovered that a large class of such theories [18,[178][179][180][181][182] possessed a 1/ -expansion [183][184][185][186][187][188][189]; that is, their Feynman graphs could be partitioned into manageable subsets, using some parameter . In fact, it was shown that the leading order sector, in the largelimit, contained an infinite but manageable number of the Feynman graphs with the topology of the -sphere ( being the rank of the tensor).…”
Section: Tensor Models and Tensor Group Field Theoriesmentioning
confidence: 99%
“…Organizing the divergences occurring in the perturbation series of rank d colored tensor graphs, one introduces the following quantity called degree of the colored tensor graph G [43,44,45] …”
Section: Rank D > 2 Colored Stranded Graphsmentioning
confidence: 99%
“…Consider then a primitively divergent subgraph S ⊂ G, and a decomposition in Hepp sectors σ , t 1 ≤ t 2 ≤ · · · ≤ t L(S) of the lines of S and introduce the usual change of variables in x k as in (44). Because S is primitively divergent, for all subgraphs S) )) ≤ 0.…”
Section: Theorem 1 (Extended Domain Of Analyticity) Consider a Tensomentioning
confidence: 99%